PENGEMBANGAN MOFIFIKASI ALAT KECEPATAN TENDANGAN TAEKWONDO - Murniwati, Murniwati; Supriatna, Eka; Purnomo, Edi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to develop new innovations in the form of electronic media that can add effectiveness to the Borneo Spirit Clab taekwondo kick measurement process.Research development or Research and Development (R&D). The research approach used in this research is procedural. The trial subject in this study was the Borneo Spirit Clab.The results of the study were questionnaires that had been validated and tested. The results of the validation by the material experts received the category "very feasible" with a value of 90% and the assessment by the media experts scored a value of 83.75% with the category "very feasible". The results of respondents or athletes get a value of 83.07% with the category "very feasible". So it can be concluded that the product of an electro-based taekwondo kick speed media tool that is developed is valid, feasible and effectively used in kick measurement. Keywords: Kick, Measurement, Taekwondo